Factors related to successful completion of a 161-km ultramarathon - Hoffman, M. D.; Fogard, K. (International Journal of Sports Physiology and Performance, 2011)
Purpose: Despite increased 161-km ultramarathon participation in recent years, little is known about those who pursue such an activity. This study surveyed entrants in two of the largest 161-km trail ultramarathon runs in North America to explore demographic characteristics and issues that affected race performance. Methods: All entries of the 2009 Western States Endurance Run and the Vermont 100 Endurance Race were invited to complete a postrace questionnaire. Results: There were 500 respondents among the 701 race entries (71.3% response). Finish time was found to have a significant (P <kleiner gleich> .01) negative association with training volume and was generally directly associated with body mass index. Among nonfinishers, the primary reason for dropping out was nausea and/or vomiting (23.0%). Finishers compared with nonfinishers were more likely (P < .02) to report blisters (40.1% vs 17.3%), muscle pain (36.5% vs 20.1%), and exhaustion (23.1% vs 13.7%) as adversely affecting race performance, but nausea and/or vomiting was similar between groups (36.8% vs 39.6%). Nausea and/or vomiting was no more common among those using nonsteroidal anti-inflammatory drugs (NSAIDs), those participating in the event with higher ambient temperatures, those with a lower training volume, or those with less experience at finishing 161-km races. Overall use of NSAIDs was high, and greater (P = .006) among finishers (60.5%) than nonfinishers (46.4%). Conclusions: From this study, we conclude that primary performance-limiting issues in 161-km ultramarathons include nausea and/or vomiting, blisters, and muscle pain, and there is a disturbingly high use of NSAIDs in these events.